Seedbank seeds for the study of environmentally induced transgenerational epigenetic variability: A case study of barley. Issue 2 (26th January 2021) - Martinelli, Tommaso; Gavazzi, Floriana; Mascheretti, Iride; Panzeri, Dario; Börner, Andreas; Lauria, Massimiliano
Abstract: Transgenerational epigenetics inheritance refers to the possibility to inherit epigenetic‐based information acquired from previous generations. The design of experiments that can measure this phenomenon presents complexities. These are related mainly to difficulties in the identification of epigenetic variation components that are independent from genetic variation, and to difficulties related to the time needed to expose genetically stable plants to different environments for several generations. In this study we propose an experimental approach that takes advantage of seed material routinely produced by seedbanks in order to circumvent the above‐mentioned issues. By taking advantage of this freely available seed material, it is possible to evaluate epigenetic differences induced by the environment experienced by previous generations and to evaluate both the extent and the impact of epigenetic variation in crops. Seeds of two barley ( Hordeum vulgare L.) cultivars, which were previously multiplied in six different seedbanks located worldwide, were grown in a common environment and the plants were evaluated at a genetic, epigenetic, and phenotypic level. Our results indicate that barley accessions multiplied in different environments displayed a comparable level of epigenetic variation, which was, however, greater than the genetic variation. Cluster analysis of methylation differences, likewise DNA differences, split the two cultivars in two distinct groups evidencing a clear link between genetic and epigenetic variation. Nevertheless, the analysis of phenotypic traits and of the CCGG sites that are variable in both cultivars suggests that there might be a possible link between previous cultivation environment and induced epigenetic changes at specific DNA regions. Core Ideas: Seedbank seeds are a useful tool for transgenerational epigenetic plasticity studies. The proposed MspI selection is a promising strategy to highlight pure epigenetic variations. Barley accessions showed interconnections between genetic and epigenetic structure. The study suggests a possible link between environment and specific epigenetic changes.